THE MOTHER GOOSE PIANO SUITE - AN AESTHETIC PARADIGM OF RAVEL’S MUSIC - Attila FODOR (Studia Universitatis Babeş-Bolyai. Musica)
The Mother Goose suite is not only one of Ravel’s most beloved works, but also a paradigmatic manifestation of his artistic thought. Composed in his impressionistic period, these musical tales reflect the composer’s dialog with several contemporary trends, like symbolism, neoclassicism or futurism, trends manifested as distinct periods of his output. In this sense, the suite form and genre appear as an optimal medium in expressing the variety in the limits of coherence. By evocating the fantastic universe of tales, Ravel reveals his childish, sensitive personality and aesthetic credo focused on the permanent aspiration to Beauty, and melancholy, as well as the fear of losing it. These principles adopted from the views of his mentor, E. A. Poe, appear in his art through a continuous pursuit of perfection, balance, compositional sophistication and refinement, elegance, playfulness and illusionism. Ravel’s motto – complexe mais pas compliqué – perfectly fits this suite, demonstrating once more, as a creative challenge, that the simplicity and richness of expression are not opposite concepts. Our study is focused on revealing the message and value configuration of the Mother Goose suite, analyzing both in a stylistic and aesthetic sense its expression devices.